Pragniemy Polski wielkiej - Jaruzelski, Wojciech (1923-2014). ([Miejsce nieznane] : [wydawca nieznany], 1982)
Afisz z cytatem.
Data wydania na podstawie treści.
Keywords: Jaruzelski, Wojciech -- (1923-2014) -- druki ulotne; Druki ulotne -- Polska -- 1970-2000.